Two cases of contact athletes with anterior cruciate ligament injuries who returned to competition early after conservative treatment with PRP therapy. (June 2022) - Hada, Shinnosuke; Ishijima, Muneaki; Omiya, Hiroyuki; Tomita, Yoshimasa; Hada, Masao
Abstract: Introduction: Anterior cruciate ligament (ACL) injuries in high-impact contact sports athletes are often treated through surgery. Recently, conservative treatment of ACL injuries in athletes using autologous biotherapy such as platelet-rich plasma (PRP) has been reported. We report two cases of aggressive conservative treatment with PRP therapy for contact athletes. Presentation of case: Case 1. A 23-year-old male rugby player with a preinjury Tegner score of 9 underwent three PRP treatments following an ACL injury and returned to preinjury levels of play 4 months postinjury. The pivot shift test had improved to grade 0 at the last follow-up. Case 2. A 34-year-old male mixed martial arts fighter with a preinjury Tegner score of 9 underwent five PRP treatments following an ACL injury and returned to his preinjury play level 3.5 months postinjury. Both contact athletes returned to competition early and continued to compete without losing stability at the final follow-up. Moreover, their functional score exceeded the median score for athletes after ACL reconstruction, suggesting satisfactory performance. Discussion: Antiinflammatory cytokines and growth factors in PRP may promote graft maturation and alter the natural history of remodeling, resulting in earlier and firmer graft maturation, improving both the duration and quality of the healing process. Conclusion: Two high-impact sports athletes with ACL injuries were treated with aggressive conservative therapy using PRP and returned early to their preinjury play level. Highlights: Conservative treatment of ACL injuries with platelet-rich plasma Two cases of aggressive conservative treatment of contact athletes with PRP therapy They returned to the same preinjury level as early as 4 and 3.5 months. Their functional score exceeded the median score of ACL reconstructed athletes. The growth factors in PRP may promote graft maturation of ruptured ACL.